Models of optimal innovation development of production systems - Боровская, Таиса Николаевна; Колесник, Ирина Сергеевна; Северилов, Виктор Андреевич; Северилов, Павел Викторович (Eastern-European Journal of Enterprise Technologies, 2014)
Formulation and solution of the problem of optimal aggregation of elements of the production system “innovations, development, production” by equivalent optimal element were presented. Production system and its elements are considered as technological resource converters. An optimal aggregation methodology, which integrates the equivalent transformations of structures of production systems and sub-optimization of subsystems was used. Generalized models of production functions - parameterized and stochastic were developed and studied. Stochastic models of parametric relations among the elements “innovations”, “development”, “production” were developed and studied. Theoretical justification of these models was performed. The new task of developing a ternary operator of optimal aggregation of the structure “innovations”, “development”, “production” was solved. Optimization variables are system resource allocation among the subsystems. The result of the operator work is the optimal equivalent production function - a data structure, in which in addition to the values of the function and appropriate resource allocations, data from previous aggregations can be preserved. The new result of the work is the information technology of developing the optimal aggregation operator for sequential structures with parametric relations in the environment of mathematical packages. The studies on the developed model, the results of which have shown the possibility of using a model of the aggregated system “innovations, development, production” for decision support were carried out.